The role of novel motor unit magnetic resonance imaging to investigate motor unit activity in ageing skeletal muscle. Issue 1 (22nd December 2020) - Birkbeck, Matthew G.; Blamire, Andrew M.; Whittaker, Roger G.; Sayer, Avan Aihie; Dodds, Richard M.
Abstract: Sarcopenia is a progressive and generalized disease, more common in older adults, which manifests as a loss of muscle strength and mass. The pathophysiology of sarcopenia is still poorly understood with many mechanisms suggested. Age associated changes to the neuromuscular architecture, including motor units and their constituent muscle fibres, represent one such mechanism. Electromyography can be used to distinguish between different myopathies and produce counts of motor units. Evidence from electromyography studies suggests that with age, there is a loss of motor units, increases to the sizes of remaining units, and changes to their activity patterns. However, electromyography is invasive, can be uncomfortable, does not reveal the exact spatial position of motor units within muscle and is difficult to perform in deep muscles. We present a novel diffusion‐weighted magnetic resonance imaging technique called 'motor unit magnetic resonance imaging (MUMRI)'. MUMRI aims to improve our understanding of the changes to the neuromuscular system associated with ageing, sarcopenia and other neuromuscular diseases. To date, we have demonstrated that MUMRI can be used to detect statistically significant differences in fasciculation rate of motor units between ( n = 4) patients with amyotrophic lateral sclerosis (mean age ± SD: 53 ± 15) and a group of ( n = 4) healthy controls (38 ± 7). Patients had significantly higher rates of fasciculation compared with healthy controls (mean = 99.1/min, range = 25.7–161.0 in patients vs. 7.7/min, range = 4.3–9.7 in controls; P < 0.05. MUMRI has detected differences in size, shape, and distribution of single human motor units between ( n = 5) young healthy volunteers (29 ± 2.2) and ( n = 5) healthy older volunteers (65.6 ± 14.8). The maximum size of motor unit territories in the older group was 12.4 ± 3.3 mm and 9.7 ± 2.7 mm in the young group; P < 0.05. MUMRI is an entirely non‐invasive tool, which can be used to detect physiological and pathological changes to motor units in neuromuscular diseases. MUMRI also has the potential to be used as an intermediate outcome measure in sarcopenia trials.